Regional Product Assortment and Customer Loyalty to the Point Of Sale - Ben Messaoud, Amira; Debabi, Mohsen (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
This paper reports the results of a quantitative study of the effect of regional product assortment on loyalty to the point of sale. In this study, we found that availability of local regional products in an assortment positively influences commitment and loyalty to the point of sale. In addition, we found that commitment mediates the effect of an assortment containing a regional product on loyalty. Finally, we found that it is possible to think of a person attached to a brand without this latter showing an observed loyalty behavior.